Comparative international accounting (Prentice-Hall, 1995)
The book provides a comprehensive on international financial reporting. Part I takes an overview of comparative international financial reporting. Many countries are considered simultaneously when examining the causes of differences, the nature and growth of multinationals and the main areas of difference. It is then possible to try put countries into groups, to look at the problems of analysis in an international context, and to examine some countries by their differences in regulation systems rather than measurement or disclosure practices. The obvious next step is to discuss the purposes and progress of international harmonization of accounting. Part II contains appendices with formats for financial statements. Part III examines particular major issues broadly and comparatively. There is also a glossary of terms that are abbreviated in some country chapters and in other publications.